Investigation on Rutting and Fatigue Cracking Susceptibility of Polystyrene Modified Asphalt - Nazim Mohamed; Demitri Ramlochan; Rean Maharaj (Advanced Aspects of Engineering Research Vol. 1, 2021)
Rutting and fatigue cracking are key rheological and performance indicators employed in asphalt technology. The use of waste polymeric materials as modifiers for the improvement of performance of asphalt pavement material has been promising. The absence of studies investigating the influence of waste polystyrene (PS) on the performance characteristics of rutting resistance and fatigue cracking resistance of the indigenous asphaltic materials Trinidad Lake Asphalt (TLA) and Trinidad Petroleum Bitumen (TPB), has hindered the possible use of PS as a performance enhancer as observed with other asphalts from different sources thus also developing a sustainable approach for the disposal of PS. The influence of PS on TLA and TPB was investigated by measuring the rheological properties of complex modulus (G*) and phase angle (\(δ\)) of prepared blends and calculating the fatigue cracking resistance and rutting resistance parameters (G*sin\(δ\) and G*/sin\(δ\) respectively). The addition of PS to TLA resulted in an increase in the fatigue cracking resistance as well as the rutting resistance compared to the pure TPB binder. Despite having improvements in rutting resistance due to PS addition, the fatigue cracking resistance of the TPB parent binders were superior compared with the PS modified TPB blends. The incremental increase in temperatures for TPB and TLA based blends resulted in gradual improvements in their fatigue cracking resistances but gradual deterioration in the rutting resistance of the modified blends. The conclusions were identical for both the Research Program Superpave specification and the Strategic Highway Research Program specifications. There is strong rheological evidence of the possibility to utilize waste PS as an asphalt performance enhancer for both TLA and TPB thus creating a sustainable strategy for the reuse of waste PS.